Solvent effects on 2-methoxyethanol conformers: an ab initio DFT study using the SCI-PCModel - Gil, Francisco P. S. C. (1999)
The four stable conformers of 2-methoxyethanol, CH3O-CH2-CH2-OH (tgg', ggg', ttg and ttt) are studied by ab initio calculations using the SCRF theory and the SCI-PCModel to assess solvent effects on the structure and vibrational spectra of this compound. Full geometry optimizations were carried out at the B3LYP/6-311+G(3df,2df,2p)//B3LYP/6-31G(d) level, and normal mode calculations were performed within the harmonic approximation using the B3LYP/6-31G(d) derived force fields. The solvent, herein represented by a polarizable continuum with a defined dielectric constant, is found to affect significantly the geometry and dipole moment of the individual solute conformers. In addition, the results seem to suggest that the intramolecular H-bond type of interactions, which occur for tgg' and ggg', tend to attenuate the solvent influence. In turn, the conformers which do not exhibit intramolecular H-bond interactions, ttg and ttt, exhibit a stronger solvent influence as revealed mainly by structural and electrostatic changes affecting both the ether O atom and the hydroxyl group.